2020
DOI: 10.1101/2020.05.14.20100834
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 management in a UK NHS Foundation Trust with a High Consequence Infectious Diseases centre: a detailed descriptive analysis

Abstract: Background: Recent large national and international cohorts describe the baseline characteristics and outcome of hospitalised patients with COVID-19, however there is little granularity to these reports. We aimed to provide a detailed description of a UK COVID-19 cohort, focusing on clinical decisions and patient journeys. Methods: We retrospectively analysed the management and 28-day outcomes of 316 consecutive adult patients with SARS-CoV-2 PCR-confirmed COVID-19 admitted to a large NHS Foundation Trust wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Baker et al found that 40.7% of 60 nursing or residential home residents with lab-confirmed COVID-19 who were admitted to a teaching hospital in Newcastle (UK) died within a 28-day period. 23 Compared to non-care home residents, the unadjusted odds ratio for death was 6.19 (95% CI 3.32-11.8).…”
Section: Evidence On Disease Incidence In Institutionalised Long-termmentioning
confidence: 96%
See 3 more Smart Citations
“…Baker et al found that 40.7% of 60 nursing or residential home residents with lab-confirmed COVID-19 who were admitted to a teaching hospital in Newcastle (UK) died within a 28-day period. 23 Compared to non-care home residents, the unadjusted odds ratio for death was 6.19 (95% CI 3.32-11.8).…”
Section: Evidence On Disease Incidence In Institutionalised Long-termmentioning
confidence: 96%
“…CFRs for 11 studies of all people at long-term care institutions facing outbreaks (including COVID-19 positive and negative residents and staff) are summarised in Table 5, 10,22,26,29,30,36,39,41,48,51,63 while CFRs for seven studies of COVID-19 positive populations are described further down. 23,25,32,38,60,67,68 For most studies included in Table 5, the source population for the identification of people with COVID-19 were all or close to all (>90%) residents or staff at long-term care institutions where an outbreak occurred. The CFR among long-term care users for these studies ranged from 0% to 33.7%, with differences in follow-up time between one and 12 weeks.…”
Section: Evidence On Disease Incidence In Institutionalised Long-termmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the shortlisted studies are summarized in Table 1. Among shortlisted studies, 23 studies were from China , nine studies were from Italy [64][65][66][67][68][69][70][71][72], ten studies were from the United States [83][84][85][86][87][88][89][90][91][92], four studies were from South Korea [75][76][77][78], three studies were from France [60][61][62], two studies were from Spain [79,80], one study each was from Belgium [35], Denmark [59], Hong Kong [63], Kuwait [73], Singapore [74], Turkey [81], and the United Kingdom [82]; and one study included data from 38 countries [93]. There were 24 studies that included hypertensive patients exclusively (100%) [36, 38, 39, 43-45, 47, 48, 50-52, 54, 56, 58, 66, 71, 72, 75, 78, 81, 87-89, 91].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%